Influence of High Temperatures on the Workability of Fresh Ready-Mixed Concrete - Sampebulu, Victor (ITB Journal Publisher, LPPM ITB, 2012)
Properties of fresh concrete made in tropical countries, which is mixed, transported (with agitation), placed and initially cured in places where the temperature ranges from about 20oC to 40oC and relative humidity above 60%, are not completely understood. Applicable requirements also differ from country to country and government agencies and private enterprises have their own specifications. Assuming such temperature and relative humidity conditions, the present study is an attempt at evaluating the properties of hot weather concrete in fresh state with using a method of readyâmixed concrete. The fresh concrete was mixed and agitated at varying concrete and ambient temperatures. Three groups of the component materials, each material having such temperature as to bring resulting temperature of the fresh concrete to about 20oC, 30oC, 35oC, were chosen. The temperature of cement was conditioned to about20o, 40oC and 60oC for each of groups respectively. The aggregate was made warm enough to simulate the condition of outdoor pile in ready-mixed concreteÂ plant. The temperature of tap water was always 20oC as it was easily controlled and unlikely affected by outdoor temperature. With the fresh concrete prevented from evaporation, slump lossÂ is caused solely by increased temperature of concrete. During agitation, the slump loss increases rapidly during the first 30 minutes but moderately during the remaining period. Concrete-placing temperature (upon arrival at the work site) could be estimated by a proposed formulaÂ derived from this study. Besides the freshly mixed concrete temperature, this formula also takes into consideration the ambient temperature, agitating time in transit and hydration heat. The achievement as described in this study may be useful to control concrete quality in terms of strength, shrinkage and other properties of concrete to be placed in hot-humid environment.